Applications of the LA-ICP-MS image mapping approach to U-Pb carbonate dating : from far-field tectonism to pedogenic nodules - Monchal, Vincent Alain (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2024)
Carbonates are one of the most common mineral phases in the upper crust, and form in many geological environments (e.g. biotic and abiotic carbonate precipitation, fracture fills in tectonic veins and ore deposits). This make carbonates an attractive target for U-Pb geochronology. LA-ICP-MS is a rapid, cost-effective tool for elemental and isotopic analyses with micron-level spatial resolution and low detection limits (ppm to ppb). Recent developments include LA-ICP-MS mapping, whereby time-integrated elemental or isotopic signals acquired by line scans (rasters) are compiled into 2D maps. This approach can be applied to U-Pb geochronology with the simultaneous acquisition of petrogenetically-diagnostic trace elements, and the maps can be spatially registered with optical microscopy, CL and / or BSE images. These image-based data are used to target regions of interest (ROIs) for U-Pb dating. This approach is ideally suited for carbonate U-Pb dating, as it can overcome major challenges inherent to the technique such as multiple growth zones, low U contents and/or variable initial Pb. U-Pb geochronology data areextracted from the ROIs and pooled into 'pseudo-analyses' to produce a spread in 238U/208Pb ratio (mu) on Concordia, resulting in better age precision. This image-based approach to LA-ICP-MS U-Pb geochronology unlocks exciting new opportunities, some of which are explored in this thesis including dating calcite veins in orogenic systems, dating carbonate concretions to improve chronological constraints in continental basins, or dating carbonate veins in mineral deposits. The image mapping approach to U-Pb carbonate dating was applied to two case studies on the Variscan Orogen in Ireland. The first case study (published in Geology in 2023) was undertaken on tightly folded Late Visean (c. 330 Ma) calciturbidites from the Carboniferous Dublin basin. The deformation has been long regarded as being Variscan in age despite being 150 km north of the Variscan front, and a variety of carbonate veins sets (tension gashes, bedding-parallel slickenfibres, breccias in fold hinges) are believed to be kinematically linked to Variscan deformation. A bedding-parallel vein with slickenfibres collected from the long limb of a flexural-slip chevron fold yieldedexceptional results, showing at least three incremental growth zones of late Eocene age. This N-S Cenozoic contraction is hitherto unrecorded on the Irish mainland and isinterpreted as Eocene reactivation of Variscan folds, like related to far field Alpine/Pyrenean shortening. The second case study is from southwestern Ireland (Fenit, Co. Kerry and the Burren Co. Clare), closer to the Variscan front. An E-W vein set yielded Variscan ages (270 and 305 Ma) that are better preserved than in the Dublin Basin, and significantly several N-S trending, vertical veins yielded Miocene ages from three localities. A period of tectonic quiescence between the Early Permian and EarlyCretaceous is common to both studies, with no evidence of vein growth or reactivation. This Miocene event has not been found before on the Irish mainland, and is attributed to N-S shortening linked to Alpine far-field stresses. Both case studies show that U-Pb geochronology on calcite veins is ideally suited to constrain the orogenic and post orogenic evolution of the shallow crust, where the low temperatures involved preclude use of other mineral systems amenable to geochronology. A third application of the U-Pb carbonate mapping technique was direct dating ofpedogenic calcite nodules from a Miocene continental sedimentary succession in the southwest of the Paris Basin. Five nodules from the same sedimentary horizon yielded U-Pb ages all within age uncertainty (yielding a 19.26 +/- 1.1 Ma central age on a radial plot) and consistent with previous biostratigraphic estimates using Neogene Mammal Zones. This result improves the local stratigraphic constraints and is the first direct dating study applied to the continental Miocene succession of the Paris Basin. It also improves regional stratigraphic correlations of continental sedimentary successions, which are often devoid of volcanic horizons or fossils assemblages with high biostratigraphic resolution. The last application explored in this thesis is related to fault controlled ore deposits, a series of carbonate veins from a 1980s PhD study on the Ballinalack Zn-Pb deposit in central Ireland. Few syn-ore or Variscan ages were preserved, with the majority of the sample set recording post-Variscan events, primarily in the Cretaceous and with some Cenozoic ages. A tectonic hiatus between the Permian and Cretaceous was observed, similar to the Dublin Basin and southwestern Ireland.
APPROVED
Keywords: Pedogenic nodules; U-Pb geochronology; Calcite; Carbonate; Ireland; Variscan; Shallow crustal deformation; Far-field tectonism